China's water resources vulnerability: A spatio-temporal analysis during 2003–2013. (20th January 2017) - Cai, Jialiang; Varis, Olli; Yin, He
Abstract: Due to the grave situation of China's water environment and aquatic ecosystems, it is of prime importance to understand the present situation of China's water resources vulnerability, and how this situation has evolved over the recent past. Consequently, we performed a comprehensive spatio-temporal analysis of China's water resources vulnerability over the period 2003–2013, using a composite index approach with an array of aspects highlighting key challenges that China's water resources system is facing. Water resources in the northern and central coasts appeared more vulnerable than in western China. China's water productivity has grown substantially over the study period, and so has safe drinking water and improved sanitation accessibility. In contrast, water pollution has been worsening remarkably in most parts of China, and so has water scarcity and shortage in the most stressed parts of the country. Graphical abstract: Highlights: China's water resources vulnerability based on socioeconomic changes was examined. An integrated and quantitative spatio-temporal analysis was performed. Water resources in China's northern and central coasts appeared more vulnerable. China's water productivity grew substantially. Water pollution has been worsening remarkably in most parts of China.